Pengembangan Snack Bar Berbasis Tepung Talas (Colocasia esculenta) dan Tepung Kacang Hijau (Vigna radiata) dengan Penambahan Bubuk Kayu Manis (Cinnamomum) - Setianingsih, Ade Nurul Sulis; Farida, Eko (Indonesian Journal of Public Health and Nutrition, 2023)
Background: The prevalence of underweight adolescents according to Riskesdas 2018 is 16.8%, which means that it has not reached the target set by WHO, it is said to be normal if the prevalence is below 10%. The factor that causes the high prevalence of underweight in adolescents is an inappropriate diet. In adolescence, snack foods have a big contribution to the total daily caloric intake. This study aims to develop a snack bar product formula as a practical snack for energy content, proximate, and organoleptic quality. This study aims to develop a snack bar product formula as a practical snack for energy content, proximate, and organoleptic quality. Methods: The experimental research design with Completely Randomized Design (CRD) was carried out in three stages, they are (1) making taro flour, mung bean flour, and cinnamon powder, and (2) making snack bars with a ratio of taro flour: mung bean flour 75%:25%(F1), 65%:35%(F2), 55%:45%(F3), cinnamon powder for the three formulations are 1%, (3) snack bar testing consists of nutritional, energy, and organoleptic content tests. The data were analyzed descriptively for nutrient and energy content and the Kruskal Wallis test followed by the Mann-Whitney test for organoleptic analysis. Results: The results of the highest energy content showed an average of 526.36 kcal/100 g, carbohydrates 58.775 g, fat 36.04 g, and protein 7.825 g. The result of the overall organoleptic test that the panelists most favored was F3 (55% taro flour: 45% mung bean flour). Conclusion: There were differences in the calorie, carbohydrate, protein, and fat content of the three formulations, and the overall organoleptic test results were favored by the panelists.